[Laiškas] / Tiškevičius Mykolas, archeologas, keliautojas, kolekcionierius - J. K. Vilčinskiui. - (:unkn) unknown (My University, 1862)
1 laiškas apie korektūros atsiuntimą ir sumokėjimą po 3 rub. už spaudos lanką.
Keywords: Rankraščiai; Laiškai; Autografų kolekcija; Tyszkiewicz, Michał, 1828-1897; Vilčinskis, Jonas Kazimieras, 1806-1885